CFD-based assessment and visualization of the failure consequences of LPG tankers. (April 2023) - Kang, Yong; Wu, Zhuang; Ma, Shuye; Zhao, Mengmeng; Li, Weixue
Abstract: This paper presents a simulation analysis of the explosions following an LPG leak and visualizes the consequences of the accident to reduce the consequences of the LPG leak explosion. Firstly, this paper proposes a CFD numerical simulation-based method for visualizing the consequences of LPG tanker failure. The method combines satellite maps and CFD numerical simulation data to visualize the consequences of LPG leaks and explosions, taking into account the influence of obstacles on the danger range of leaks and explosions; Secondly, this paper applies the method to a liquefied petroleum gas accident that occurred in the Wenling section of the Shenhai Expressway and performs CFD numerical simulation on the accident process and visualizes the consequences of the accident. Therefore, this method can provide a theoretical reference for the prior prevention of LPG accidents and the analysis of the consequences of accidents, as well as certain practical guidance instructive. Highlights: Propose a method for visualizing the consequences of accidents. Analysis of an LPG tanker accident. Obstacle-influenced blast overpressure distribution pattern obtained. Visual analysis of an LPG tanker accident.